1994
DOI: 10.2166/wst.1994.0587
|View full text |Cite
|
Sign up to set email alerts
|

Microbial structure and activity of UASB granules treating different wastewaters

Abstract: The microstructure of three types of UASB granules respectively treating sucrose, glutamate and brewery wastewaters in mesophilic conditions were analyzed by light, scanning electron and transmission electron microscopies, along with the specific methanogenic activity (SMA) of the granules. Results showed that the granule's microstructure was dependent on the nature of the substrate. Those degrading soluble carbohydrates exhibited a layered structure, while those degrading glutamate exhibited a rather uniform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
78
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(86 citation statements)
references
References 0 publications
7
78
1
Order By: Relevance
“…This m ay be directly related to the differences observed in the granules. Fang et al (1994) verified that acetoclastic Methanosaeta were the key structural granules from UASB reactor treating different substrates. Filamentous microorganisms and Methanoseata-like cells seem to have a structural role, producing stability of the pellets formed.…”
Section: Resultsmentioning
confidence: 72%
“…This m ay be directly related to the differences observed in the granules. Fang et al (1994) verified that acetoclastic Methanosaeta were the key structural granules from UASB reactor treating different substrates. Filamentous microorganisms and Methanoseata-like cells seem to have a structural role, producing stability of the pellets formed.…”
Section: Resultsmentioning
confidence: 72%
“…As a result, the insight in the mechanism of the sludge granulation process for anaerobic treatment has been elucidated sufficiently, at least for practical application (e.g. De Zeeuw 1982Hulshoff Pol and Lettinga 1986;Wiegant and de Man 1986;Hulshoff Pol et al 1987Dolfing 1987;Wu et al 1991;van Lier et al 1994;Fang et al 1994;Liu et al 2003;Song et al 2010;Habeeb et al 2011;Abbasi and Abbasi 2012;Subramanyam 2013). Granulation can proceed under mesophilic, thermophilic and psychrophilic conditions.…”
Section: Sludge Granulationmentioning
confidence: 99%
“…Similar findings have been reported in the study of Baloch et al (2008), in which anaerobic granules were found to possess a multi-layered structure with complex microbial ecology and dominating methanogenic subpopulations. Apparently, Methanosaeta plays an important role in sludge granulation (Fang et al 1994). The structured characteristics and layered 'ecological zones' of the granules were defined as a stable metabolic arrangement that creates optimal nutritional and environmental conditions for all microorganisms included in it (Guiot et al 1992).…”
Section: Sludge Granulationmentioning
confidence: 99%
See 1 more Smart Citation
“…This reactor has been successfully applied for high-rate anaerobic wastewater treatment. The success of UASB depends on the formation of active and able granules (Fang et al 1994). These granules consist of self-immobilized, compact form of aggregate of organisms and lead to an effective retention of organisms in the reactor (Akunna and Clark 2000).…”
Section: Upflow Anaerobic Sludge Blanket (Uasb) Reactorsmentioning
confidence: 99%